Sexually abusive behaviour among young sexual abused or physical abused Icelandic males and females: The mediating effect of anger and depressed mood - Sandra Sif Sæmundsdóttir 1990- (2013)
It is believed that individuals under the age of 17 are responsible for about 20% of all sexual offences. There are various factors that contribute to this behaviour and this topic has been the subject in numerous studies aimed at finding what factors sexual offenders have in common. This study investigated whether males were more likely to report sexual offending and if those who report sexual offending also reported history of sexually abuse and history physical abuse. Anger and depressed mood were also looked at in regards to weather or not these factors mediated the effect of sexual abuse and physical abuse on sexual offending. The sample used in this study consisted of 7430 participants, all students in 9th and 10th grade in secondary schools in Iceland with mean age of 15.5 years. Correlations, one-way ANOVA and binary logistic regression were used to test for the main interaction and mediating effects. The results of this study indicated that being a male, reporting a history of sexual abuse and physical abuse and experiencing anger independently predicts reporting sexual offending. Furthermore, anger turned out to partially mediate the relationship between sexual abuse and physical abuse and sexual offending. Talið er að börn, 17 ára og yngri, séu ábyrg fyrir um 20% allra kynferðisbrota. Ýmsir þættir geta stuðlað að þessari hegðun og eru margar rannsóknir sem skoða hvað þessir einstaklingar eiga sameiginlegt. Í þessari rannsókn var skoðað hvort strákar væru líklegri til að vera gerendur kynferðisofbeldis og hvort að þeir einstaklingar sem að segjast hafa þvingað einhvern til kynferðisathafna eða samfara séu líklegri til að eiga sjálfir sögu um kynferðislegt ofbeldi og/eða líkamlegt ofbeldi. Einnig var skoðað hvort reiði og þunglyndi miðluðu áhrifum kynferðisobeldis og líkamlegs ofbeldis á að vera gerandi kynferðisofbeldis. Þátttakendur rannsóknarinnar voru 7430 nemendur í 9. og 10. bekk allra grunnskóla á Íslandi og var meðalaldur þátttakanda 15,5 ára. Fylgnigreining, dreifigreining og aðhvarfsgreining ...